Effects of health education on choice of delivery mode and fear related to childbirth among primigravidae in Hamadan, Iran - Matinnia, Nasrin (2014)
The choice of delivery method is a concern of the third trimester and a critically important decision during pregnancy. Naturally, this brings up a question regarding the safety of both mother and child. The rates of Caesarean Section in many countries have increased in spite of the known risks of this procedure. Caesarean Sections by maternal request also play a role in increasing the overall caesarean rate in the world. The rate of caesarean sections was 47.5% and 79.1% in public and private hospitals respectively in Hamadan province in 2012, the West part of Iran. The present study aims to evaluate the effectiveness of health education on the choice of delivery method among primigravidae in Hamadan, Iran. A randomized controlled trial design was conducted based on the Health Belief Model. This study investigates the effect of a health education programme on fear related to childbirth, beliefs and choice delivery method among Primigravidae. The sampling method was multi-stage random sampling in which 342 primigravidae was randomly selected based on inclusion and exclusion criteria. They were randomized to either the two intervention groups or the control group. The reliable and valid tools in this study were included Rosenberg Self Esteem Scale,Perceived Stress scale, Revised Dyadic adjustment Scale, Multidimensional Scale of Perceived Social Support, Revised Fear related to Childbirth Scale and the Health Belief Model Scale. An educational module on prenatal health education was developed. The ultimate goals of the educational intervention were reducing fear related to childbirth, changing beliefs about natural childbirth and decreasing request a caesarean section. The two educational methods tested in this study; the discussion group and the booklet. All materials of four sessions in the discussion group are similar to four sections of the booklet as well as their time. The primigravidae received the four sections of the booklet or four two-hour sessions every 4 weeks after pretest, while the control group received the routine prenatal education. The duration of intervention was 16 weeks and post test was conducted after four weeks of the last education. Both programmes were delivered by trained peers. Two-way repeated measure ANOVA was applied to assess the effectiveness of the intervention. The outcome measures were assessed at pretest and post test. There were significant difference in the mean scores of self esteem (p=.005) and perceived stress (p<.001) in comparison with the control group. Conversely, there were no differences in the mean scores of quality of marital relationship and perceived social support between groups. These scales were considered as influencing factors in fear related to childbirth. There were significant main effects for group [F = 14.6, p < 0.001, η2=0.08]; time [F = 40.7, p< 0.001, η2= 0.11] and group x time interaction [F =110.68, p < 0.001, η2= 0.4] for fear related to childbirth. Similarly, the main effects for group [F = 24.764, p <0.001, η2=0.13], time [F = 362.57, p < 0.001, η2=0.475], and group x time interaction [F= 104.24, p= < 0.001, η2=0.611] were significant regarding beliefs. The request of a caesarean section was significantly different (χ2 =10.94, p=0.004) between intervention groups and control group. The prenatal health intervention programme was effective in decreasing fear related to childbirth and changing the behaviour related to request a caesarean section. The rate of choice of caesarean section was reduced after intervention among primigravidae in Hamadan.